2022
DOI: 10.1177/08850666221111776
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Existing Right Ventricular Dysfunction as an Independent Risk Factor for Post Intubation Cardiac Arrest and Hemodynamic Instability in Critically Ill Patients: A Retrospective Observational Study

Abstract: Background Post intubation cardiac arrest and hemodynamic instability are serious adverse events encountered in critically ill patients. The association of pre-existing right ventricular (RV) dysfunction with post intubation cardiac arrest and hemodynamic instability in critically ill patients is unknown. Methods This is a retrospective matched cohort study of adult critically ill patients who underwent intubation from July 2016 to December 2019. The study was conducted at a quaternary medical center in Housto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Halliday et al identified hypotension, the need for vasopressors prior to intubation, age, and cirrhosis as the top four risk factors in a secondary analysis of trial data [10][11][12][13]. Right ventricular (RV) dysfunction is also an increasingly appreciated risk factor as perturbations in gas exchange, acid/base status, and intrathoracic pressure may all lead to cardiovascular collapse [14,15]. In a secondary analysis of INTUBE, the risk factors for cardiovascular instability included age, lower blood pressure, lower oxygen saturation, and propofol administration [16].…”
Section: Which Patients Are At Risk?mentioning
confidence: 99%
“…Halliday et al identified hypotension, the need for vasopressors prior to intubation, age, and cirrhosis as the top four risk factors in a secondary analysis of trial data [10][11][12][13]. Right ventricular (RV) dysfunction is also an increasingly appreciated risk factor as perturbations in gas exchange, acid/base status, and intrathoracic pressure may all lead to cardiovascular collapse [14,15]. In a secondary analysis of INTUBE, the risk factors for cardiovascular instability included age, lower blood pressure, lower oxygen saturation, and propofol administration [16].…”
Section: Which Patients Are At Risk?mentioning
confidence: 99%
“…To identify such patients, bedside ultrasound evaluation has been suggested. 12 While few studies have evaluated the role of transthoracic echocardiography in the critically ill patient requiring intubation, bedside transthoracic echocardiography (TTE) may reveal RV failure not clinically evident, identify wall motion abnormalities suggestive of myocardial ischemia, provide an estimate of volume status, and facilitate a diagnosis of pulmonary embolism or tamponade. Using TTE to identify patients with cardiogenic shock may then facilitate the resolution of modifiable preoperative risk factors and inform the choice of airway management technique.…”
Section: Airway Management In Cardiogenic Shockmentioning
confidence: 99%
“…A retrospective 2023 study in critically ill patients found an independent association of pre-intubation moderate to severe right ventricular dysfunction with postintubation hemodynamic instability and cardiac arrest. To identify such patients, bedside ultrasound evaluation has been suggested 12 . While few studies have evaluated the role of transthoracic echocardiography in the critically ill patient requiring intubation, bedside transthoracic echocardiography (TTE) may reveal RV failure not clinically evident, identify wall motion abnormalities suggestive of myocardial ischemia, provide an estimate of volume status, and facilitate a diagnosis of pulmonary embolism or tamponade.…”
Section: Introductionmentioning
confidence: 99%